Moderating Effect of Teaching Etiquette on Intercultural Sensitivity and Work Fulfillment of Teachers in Maa District, Davao City - Sarpamones, Glory Khing S. (PPSDP International Journal of Education, 2024)
The current study was set to evaluate whether teaching etiquette significantly moderate the relationship between intercultural sensitivity and work fulfillment of teachers. In this study, the researcher selected the 200 public elementary school teachers in Maa District, Davao City as the respondents of the study. Stratified random sampling technique was utilized in the selection of the respondents. Non-experimental quantitative research design using descriptive-correlational method was employed. The data collected were subjected on the following statistical tools: Mean, Pearson Moment Product Correlation, and Hierarchical Regression Analysis. Descriptive analysis showed that teaching etiquette and work fulfillment were described as extensive, while, intercultural sensitivity of teachers was rated as moderately extensive. Further, correlation analysis demonstrated that there is significant relationship among intercultural sensitivity, work fulfillment, and teaching etiquette of teachers in Davao Central District, Davao City. Evidently, hierarchical regression analysis proved that professional etiquette significantly moderates the interaction between intercultural sensitivity and work fulfillment of teachers in Maa District, Davao City. In other words, teaching etiquette is a significant moderator on the intercultural sensitivity and work fulfillment of teachers since it strengthens its relationship. The study, therefore, conducted for further utilization of findings through publication in reputable research journal.